2014
DOI: 10.1097/jto.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Non–Small-Cell Lung Cancer After Breast Cancer: A Population-Based Study of Clinicopathologic Characteristics and Survival Outcomes in 3529 Women

Abstract: BC survivors are more likely to be diagnosed with earlier stage NSCLC versus first primary NSCLC patients, perhaps reflecting heightened surveillance compared with the general population. In contrast to prior studies of NSCLC in survivors of lymphopoietic malignancies, BC history does not appear to adversely affect OS after NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 45 publications
9
25
1
Order By: Relevance
“…These patients also more often treated with surgery and not radiation compared to NSCLC patients without previous malignancy. This was reported in breast cancer survivors who developed NSCLC and was also postulated to be due to heightened surveillance 25 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These patients also more often treated with surgery and not radiation compared to NSCLC patients without previous malignancy. This was reported in breast cancer survivors who developed NSCLC and was also postulated to be due to heightened surveillance 25 .…”
Section: Discussionmentioning
confidence: 90%
“…Standardized incidence ratios (SIRs), defined as the ratio of observed over expected (O/E) rates of NSCLC cancers were calculated and adjusted by person-years at risk 24, 25 . The observed value was derived by looking at those patients who developed NSCLC (numerator) after the first primary of interest and was divided by all patients diagnosed with the same primary but who did not develop NSCLC (denominator).…”
Section: Methodsmentioning
confidence: 99%
“…In other cases the increased risk results from historical exposure to a carcinogen such as cigarette smoke [23,24]. In many such cases the diagnosis of lung cancer is the primary driver of future life expectancy, for example accounting for 12% of deaths in (HNSCC) patients in the Surveillance Epidemiology and End Results (SEER) database [24] and for 100% of cancer related deaths reported in a recently reported small cohort of early stage bladder cancer patients with a second primary lung malignancy [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision‐making for patients presenting with lung‐2 sometimes can be challenging because of the limited and conflicting information on prognosis. A study of Hodgkin lymphoma patients who developed lung‐2 showed inferior overall survival of lung‐2 compared to lung‐1, whereas the overall survival of lung‐2 among breast cancer survivors was not worse compared to lung‐1 . The reduced overall survival (if any) is, however, not surprising, given the non‐negligible mortality contribution of the first primary cancer, and does not necessarily indicate more aggressive behavior of lung‐2.…”
Section: Introductionmentioning
confidence: 98%